2014
DOI: 10.3389/fphys.2014.00260
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-hydroxybutyrate, its polymer poly-β-hydroxybutyrate and inorganic polyphosphate in mammalian health and disease

Abstract: We provide a comprehensive review of the role of β-hydroxybutyrate (β-OHB), its linear polymer poly-β-hydroxybutyrate (PHB), and inorganic polyphosphate (polyP) in mammalian health and disease. β-OHB is a metabolic intermediate that constitutes 70% of ketone bodies produced during ketosis. Although ketosis has been generally considered as an unfavorable pathological state (e.g., diabetic ketoacidosis in type-1 diabetes mellitus), it has been suggested that induction of mild hyperketonemia may have certain ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 222 publications
(393 reference statements)
2
78
0
Order By: Relevance
“…Two main ketone bodies, beta-hydroxybutyrate (BHB) and acetoacetate (ACA) which we named ketones, are generally regarded as energy carriers. 6 Ketones are consumed by the brain as a main source of energy source when glucose is limited. 7 Our previous in vitro data showed that ketones decreased the NADH level when neurons were subjected to glutamate excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Two main ketone bodies, beta-hydroxybutyrate (BHB) and acetoacetate (ACA) which we named ketones, are generally regarded as energy carriers. 6 Ketones are consumed by the brain as a main source of energy source when glucose is limited. 7 Our previous in vitro data showed that ketones decreased the NADH level when neurons were subjected to glutamate excitotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 3HB treatment with or without CR elevated retinal fumarate accompanied by TCA cycle`s enzymes involved in ketolysis and fumarate synthesis, being independent of changes in the energy status, indicating that the late phase of the TCA cycle rather than the first phase is essential for fumarate elevation. In addition, the energy substrates responded to gluconeogenesis other than ketone bodies, fatty acids, amino acids, and carbohydrates, and they did not share intermediate conversion processes of the TCA cycle in the course of entry into this cycle (Dedkova & Blatter, 2014). Thus, herein, the elevation of the Nrf2 activator, fumarate, may be due to the unique characteristics of ketone metabolism, namely the activation of TCA cycle flux by the upregulation of a concomitant process of TCA cycle intermediate conversion and ketolysis in response to prominent sustained supplementation of 3HB in an energy shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, it has been recently reported that β-hydroxybutyrate, a fundamental contributor to cardiac energy metabolism in conditions of prolonged exercise [32] can cause HDAC inhibition and consequent protection against oxidative stress [33]. It is therefore conceivable that the factor linking electrical activity to reduced HDAC activity is a metabolic factor.…”
Section: Discussionmentioning
confidence: 99%